Covid-19 And Its Effects on Fish Production and Fishermen Income: Evidence from Pondokdadap Fishing Port in Indonesia - Muntaha, Ali; Sunardi, Sunardi; Sulkhany, Eko; Siahaan, Ian Bernard (Faculty of Fisheries and Marine Science, Brawijaya University, 2023)
The COVID-19 pandemic has caused unprecedented disruption to the global economy and society, including fisheries and aquaculture. This study aims to analyze the impact of COVID-19 on the fisheries sector in Indonesia, focusing on the case of Pondokdadap Fishing Port, one of the main landing sites for tuna and other pelagic fish in East Java Province. This study compared data from 2019 (before the pandemic) and 2020 (during the pandemic) to assess changes and trends in the volume and value of fish production, the number of fishing trips, fish prices, and fishers' income at Pondokdadap Fishing Port. This study found that COVID-19 has significantly reduced the volume and value of fish production, the number of fishing trips, fish prices, and fishers' income at Pondokdadap Fishing Port. There are several possible causes and consequences, such as decreased demand, supply chain disruption, health risks or food insecurity. This research also identifies several policy responses and recommendations to mitigate the negative impacts and enhance the recovery of the fisheries sector, such as providing income support, facilitating market access, improving health measures, or strengthening policies on the capture fisheries sector. This research contributes to filling a gap in the literature on the impact of COVID-19 on fisheries in developing countries, particularly Indonesia.